A poly(ascorbyl acrylate)-containing nanoplatform with anticancer activity and the sequential combination therapy with its loaded paclitaxel. Issue 40 (3rd October 2016) - Song, Yufeng; Xie, Yanqi; Yang, Junjiao; Li, Ruiqiong; Jin, Xu; Yang, Jing
Abstract : The complex nanocarriers combined with the loaded therapeutic agents to achieve synergistic tumor inhibition. Abstract : Despite progress, the combination therapy of a nanoscale delivery system and its loaded drug to increase the efficiency of anticancer treatment still remains a challenge. In this study, taking advantage of ascorbic acid with anticancer activity, complex nanovehicles were designed and constructed by co-assembly of the amphiphilic block polymers poly(ascorbyl acrylate)- block -poly(lactic acid) (PAA- b -PLA) and maleimide-decorating poly(ethylene glycol)- block -poly(lactic acid) (Mal-PEG- b -PLA) in aqueous solution. The combination of the nanoparticles' large surface and structural repeating characteristics of PAA led to an exponential increase in the ascorbyl content on the nanoparticle surface, which endowed the nanovehicles themselves with desired anticancer activity. In vitro cytotoxicity assays against normal cell line NIH3T3 and breast cancer cell line MCF-7 demonstrated that PAA- b -PLA/Mal-PEG- b -PLA complex nanoparticles exhibited benign biocompatibility against normal cells and prominent cancer inhibition ability. Paclitaxel (PTX)-loaded complex nanoparticles against MCF-7 were further investigated by MTS assay and flow cytometry. As a result, a synergistic effect of the complex nanoparticles and the loaded PTX in inducing cancer cell apoptosis was apparently noted. The newly developed PAA- b -PLA/Mal-PEG- b -PLA complex nanoparticles not only served as an effective and safe vector to deliver the therapeutic agents to the targeted site, but more importantly, they could also combine with the loaded therapeutic agents to achieve a synergistic effect for improving tumor inhibition efficiency.